EFEKTIVITAS PENGGUNAAN MOBILE HEALTH DALAM MENURUNKAN FAKTOR RISIKO YANG DAPAT DIMODIFIKASI PADA OBESITAS - Putra, Mepsa; Mulyono, Sigit; Zulka , Khairat (Alauddin Scientific Journal of Nursing, 2023)
Overweight and obesity are contributors to morbidity and mortality rates in the world. A comprehensive lifestyle approach (diet, behavioral therapy and physical activity) and innovative weight management nursing interventions in primary health care are needed in handling these cases. One of the handling methods is monitoring of weight loss program interventions using a mobile health application (mHealth). Smoking, nutrition, alcohol and physical activity are modifiable risk factors and contribute health burden disease. The aim of this study was to evaluate the impact and outcomes of mobile phone applications on people who are overweight or obese. The study and review of 7 journal articles related to the use of mobile health in weight loss management was carried out on various types of mobile applications such as mobile apps, phone calls, text messages and others. The result is that the use of mobile health applications will get a more effective combination intervention for weight loss and disease prevention and the burden of health problems.